Serum albumin corrected anion gap levels are associated with poor prognosis in patients with acute ischemic stroke - Yaxin Zhang; Fan Wu; Jiawei Sun; Chuchuan Xu; Qingwei Yang; Guangdong Wang (Scientific Reports)
Abstract Acute ischemic stroke (AIS) remains a major cause of global morbidity and mortality. This study aimed to evaluate the role of albumin corrected anion gap (ACAG) as a prognostic marker for AIS patients. We analyzed data from 1014 AIS patients in the MIMIC-IV database, stratifying patients by ACAG levels. Using Cox proportional hazards models, restricted cubic splines, and Kaplan-Meier survival analysis, we assessed the relationship between ACAG and both 30-day and 365-day mortality. Our results show that elevated ACAG levels are significantly associated with higher mortality rates at both time points. The hazard ratios for 30-day and 365-day mortality were 1.07 (95% CI 1.04–1.11, P < 0.001) and 1.06 (95% CI 1.03–1.09, P < 0.001), respectively. Receiver operating characteristic (ROC) analysis showed that the area under the curve (AUC) of ACAG for predicting 30-day and 365-day mortality was 0.666 and 0.662, respectively. Subgroup analysis revealed significant interactions with gender and sepsis status. A nomogram incorporating ACAG and other key variables achieved AUCs of 0.748 and 0.765 for predicting 30-day and 365-day mortality, respectively. These findings indicate that elevated ACAG is an independent risk factor for both short-term and long-term mortality in AIS patients. Its incorporation into clinical practice may enhance the ability of clinicians to identify high-risk patients early, enabling timely and targeted interventions.